36th AIAA/ASME/SAE/ASEE Joint Propulsion Conference and Exhibit 2000
DOI: 10.2514/6.2000-3397
|View full text |Cite
|
Sign up to set email alerts
|

Fastrac nozzle design, performance and development

Abstract: With the goal of lowering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On the other hand, published papers [1,2] have reported that a number of researchers have conducted heat flux estimations of the combustor's inner surface in two different ways.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, published papers [1,2] have reported that a number of researchers have conducted heat flux estimations of the combustor's inner surface in two different ways.…”
Section: Introductionmentioning
confidence: 98%